Impaired emotional awareness is associated with childhood maltreatment exposure and positive symptoms in schizophrenia - Beals, Kendall; Torregrossa, Lénie J.; Smith, Ryan; Lane, Richard David; Sheffield, Julia M. (Frontiers in Psychiatry, 2024)
Objectives: Evidence suggests that emotional awarenessthe ability to identify and label emotionsmay be impaired in schizophrenia and related to positive symptom severity. Exposure to childhood maltreatment is a risk factor for both low emotional awareness and positive symptoms.Methods: The current investigation examines associations between a performance-based measure of emotional awareness, positive symptom severity, and childhood maltreatment exposure in 44 individuals with a schizophrenia-spectrum disorder and 48 healthy comparison participants using the electronic Levels of Emotional Awareness Scale (eLEAS), Positive and Negative Syndrome Scale (PANSS) and Childhood Trauma Questionnaire (CTQ).Results: Patients demonstrated significant deficits in emotional awareness overall , which was true for both self and others. In patients, lower emotional awareness was significantly associated with more severe positive symptoms. Emotional awareness was significantly impaired in patients with schizophrenia with self-reported maltreatment exposure, relative to other groups. Severity of maltreatment was not significantly associated with emotional awareness or positive symptoms when looking continuously, and there was no significant indirect effect.Conclusions: These data suggest that emotional awareness impairments observed in schizophrenia may be exacerbated by exposure to childhood maltreatment, possibly putting individuals at greater risk for experiencing positive symptoms of psychosis.